2x-y=-6

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract 2x from both sides of the equation.

-y=-6-2x

Multiply each term in -y=-6-2x by -1

Multiply each term in -y=-6-2x by -1.

(-y)⋅-1=(-6)⋅-1+(-2x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=(-6)⋅-1+(-2x)⋅-1

Multiply y by 1.

y=(-6)⋅-1+(-2x)⋅-1

y=(-6)⋅-1+(-2x)⋅-1

Simplify (-6)⋅-1+(-2x)⋅-1.

Simplify each term.

Multiply -6 by -1.

y=6+(-2x)⋅-1

Multiply -1 by -2.

y=6+2x

y=6+2x

Reorder 6 and 2x.

y=2x+6

y=2x+6

y=2x+6

y=2x+6

Using the slope-intercept form, the slope is 2.

m=2

Find the Slope 2x-y=-6